Chapter The Fruit of the Tree of Life Ritual Interpretation of the Crucifixion in the Gospel of Philip - Lundhaug, Hugo (De Gruyter, 2014)
The Gospel of Philip, preserved only in Nag Hammadi Codex II,1 has proven to be a difficult text for its modern interpreters. In addition to its numerous lacunae, scholars have consistently been frustrated by its seemingly haphazard structure and highly allusive rhetoric, leading some to regard it as simply a collection of excerpts, rather than as a coherent composition in its own right.2 Still, the Gospel of Philip is nevertheless one of the most discussed texts of the Nag Hammadi Codices and one of the texts that crop up most often in discussions on ancient "Gnosticism" or "Valentinianism,"3 while in relation to NT studies the text is of interest with regard to its rhetorical dependence on NT allusions. Yet there is presently no consensus as to the date and provenance of the text nor its nature and purpose. In the present article I aim to show how a methodology inspired by cognitive linguistics, more specifically Blending Theory, may help us under-stand how the Gospel of Philip makes sense. As an example, I use Blending The-ory to analyze the way in which the tractate interprets the crucifixion in light of Scripture on the one hand and ritual practice on the other, and thereby try to show how the Gospel of Philip may in fact be read as a coherent theological statement, at least in this regard. This is an especially useful example as it has been claimed that, in the Gospel of Philip, "the Cross is viewed as an historic event, but hardly as the source of redemption, the sacraments, or spiritual knowledge."4 In light of the common practice of analyzing the Nag Hammadi writings on the basis of scholarly constructions of "Gnosticism," such a conclusion is hardly surprising.5 On closer inspection, however, the crucifixion seems to play a rather more central role in the soteriology and rhetorics of the Gospel of Philip than such a conclusion would suggest, as will be shown in what follows.